Ovarian Function Modulates the Effects of Long-Chain Polyunsaturated Fatty Acids on the Mouse Cerebral Cortex - Herrera, Jose L.; Ordoñez-Gutierrez, Lara; Fabrias, Gemma; Casas, Josefina; Morales, Araceli; Hernandez, Guadalberto; Acosta, Nieves G.; Rodriguez, Covadonga; Prieto-Valiente, Luis; Garcia-Segura, Luis M.; Alonso, Rafael; Wandosell, Francisco G. (Frontiers in Cellular Neuroscience, 2018)
Different dietary ratios of n-6/n-3 long-chain polyunsaturated fatty acids (LC-PUFAs) may alter brain lipid profile, neural activity and brain cognitive function. To determine whether ovarian hormones influence the effect of diet on the brain, ovariectomized and sham-operated mice continuously treated with placebo or estradiol were fed for three months with diets containing low or high n-6/n-3 LC-PUFA ratios. The fatty acid (FA) profile and expression of key neuronal proteins were analyzed in the cerebral cortex, with intact female mice on standard diet serving as internal controls of brain lipidome composition. Diets containing different concentrations of LC-PUFAs greatly modified total FAs, sphingolipids and gangliosides in the cerebral cortex. Some of these changes were dependent on ovarian hormones, as they were not detected in ovariectomized animals, and in the case of complex lipids, the effect of ovariectomy was partially or totally reversed by continuous administration of estradiol. However, even though differential dietary LC-PUFA content modified the expression of neuronal proteins such as synapsin and its phosphorylation level, PSD-95, amyloid precursor protein (APP) or glial proteins such as glial fibrillary acidic protein (GFAP), an effect also dependent on the presence of the ovary, chronic estradiol treatment was unable to revert the dietary effects on brain cortex synaptic proteins. These results suggest that, in addition to stable estradiol levels, other ovarian hormones such as progesterone and/or cyclic ovarian secretory activity could play a physiological role in the modulation of dietary LC-PUFAs on the cerebral cortex, which may have clinical implications for post-menopausal women on diets enriched with different proportions of n-3 and n-6 LC-PUFAs.